Is training to failure a safe and effective method for improving athletic performance? - Khamoui, A. V.; Willardson, J.; Dawes, J. (Strength and Conditioning Journal, 2011)
Training to failure is a popular training method used to improve muscular strength, size, and endurance. At this time, the value of this training strategy for improving athletic performance is a topic of considerable debate. In this column, the potential benefits and detriments of this training method will be presented.